CSR and Corporate Sustainability: The Mediating Roles of Financial Performance and Legitimacy - Linda Yuliani Hutadjulu (jfpublisher, 2026)
Corporate social responsibility (CSR) has evolved from a philanthropic obligation into a strategic instrument through which firms pursue long-term sustainability. Despite growing scholarly interest, the mechanisms connecting CSR to sustainability outcomes remain insufficiently examined, particularly in developing economy contexts. This study investigates how CSR contributes to corporate sustainability through two parallel mediating pathways, financial performance and social legitimacy, drawing on legitimacy theory, stakeholder theory, and positive accounting theory as an integrated analytical framework. A systematic literature review of Scopus-indexed publications from 2021 to 2025 was conducted, with findings synthesised through classification, thematic analysis, and critical evaluation. The results confirm that CSR positively influences corporate sustainability, financial performance, and institutional legitimacy, supporting all three hypotheses proposed. These effects are conditional on implementation quality and the institutional environment in which firms operate. In emerging markets, including Indonesia, firms frequently adopt CSR in response to regulatory pressure rather than genuine strategic commitment, which constrains the financial and legitimacy gains that substantive engagement would otherwise generate. This study extends prior research by showing that financial performance and legitimacy function as simultaneous and mutually reinforcing mediators rather than independent channels, and it challenges the assumption that a positive CSR-sustainability relationship is universally applicable. The findings offer practical guidance for firms and policymakers in developing economies navigating rapidly expanding sustainable finance regulations.